Comparison between Double-Guidewire and Single-Guidewire Techniques to Serum Amylase and Lipase Levels at 24 Hours after Endoscopic Retrograde Cholangiopancreatography - Anuchapreeda, Soros; Moungthard, Hathaiwan; Limthanetkul, Nisakorn; Phengsuthi, Patduangpuk; Wannasu, Ratchadaporn; Buachoey, Janejira; Peeratippayamongkol, Chumpol (Journal of The Department of Medical Services, 2021)
Background : Serum amylase and lipase are frequently checked for evaluating acute pancreatitis in patients who developed abdominal pain after ERCP procedure. In difficult cases of ERCP, double-guidewire technique would be recommended to increase success rate of cannulation but it might affect on rising of serum amylase and lipase levels. Objective : This study aims to comparison between double-guidewire technique (DGW) and single-guidewire technique (SGW) to serum amylase and lipase levels at 24 hours after ERCP. Method : The study was observational analytic study in patients who visited at National Cancer Institute and Lopburi Cancer Hospital from February 2019 to February 2020 for ERCP. Result : All 78 patients were included, most of indication for ERCP is malignant biliary tract obstruction about 62.8%. Amylase level rising above 3 times of normal limit was statistically significant in DGW group (53.8% and 23.5% respectively, p=0.008) nevertheless no significant difference of the lipase level between the two groups. Regards to multiple logistic regression, DGW group showed correlation to rising amylase level than SGW group but statistically was not significant (OR 2.0, 95% CI = 0.61, 6.52, p = 0.252). Conclusion : Double-guidewire technique group has many confounding factors that affect amylase level such as first episode of ERCP, cannulation times more than 10 minutes, and sphincterotomy. Therefore, DGW group showed statistically significant rising of amylase level at 24 hours compare to SGW group.